(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A weed survey was conducted in seven locations in Dongolaarea during the winter season of 2008/2009 to determine the mostprevalent weed species associated with wheat (Triticum aestivum L.). Astratified random sampling procedure was adopted and each location wasdivided into fields, of which 10 were randomly selected. Number ofindividual weed species was determined in 10 quadrates, each 1 m 2 . Thefield density, field frequency, field uniformity, relative field density,relative field frequency, relative field uniformity and relative abundanceof the species were determined. The data revealed the presence of 29species of annual and perennial weeds belonging to 15 families. Thehighest number of species occurred in Elmasakeen and Sheikh Shareef,while the lowest was recorded in Selaim basin. Sinapis arvensis, Cynodondactylon, Malva palviflora, Convolvulus arvensis, Chenopodium albumand Sorghum arundinaceum occurred at high relative abundance. Specieswith moderate relative abundance were Cyperus rotundus, Trigonellahamosa, Eruca sativa, Chenopodium murale and Sinapis alba. The otherspecies occurred in few locations and exhibited low to very low relativeabundance